Thickness Influence on Structural and Optical Properties of ZnO Thin Films Prepared by Thermal Evaporation - Abed, E. y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Zinc Oxide transparent thin films (ZnO) with different thickness from (220 to 420)nm Â±15nm were prepared by thermal evaporation technique onto glass substrates at 200 with the deposition rate of (10 2) nm sec-1, X-ray diffraction patterns confirm the proper phase formation of the material. The investigation of (XRD) indicates that the (ZnO) film is polycrystalline type of Hexagonal and the preferred orientation along (002) plane. The Optical properties of ZnO were determined through the optical transmission method using ultraviolet-visible spectrophotometer with wavelength (300 â€“ 1100) nm. The optical band gap values of ZnO thin films were slightly increased from (2.9 - 3.1) eV as the film thickness increased. thin films; structural properties; optical band gap.